Surzhyk: transformation of perception in the Ukrainian mass consciousness about the mixed Ukrainian-Russian idiom in the context of current socio-political events in Ukraine - Fuderer, Tetyana (Poznańskie Studia Slawistyczne, 2025)
This research analyzes the changes in perception about the mixed Ukrainian-Russian idiom (surzhyk) in the Ukrainian mass consciousness in the conditions of military aggression of the Russian Federation on Ukraine, which requires a revision of linguistic approaches in its study. The existence of colonial origin concepts of Ukrainian-Russian bilingualism in Ukrainian linguistics, which led to the emergence of numerous mixed speech forms, is explained. The negative attitude towards the mixed Ukrainian-Russian speech forms is interpreted in the context of neo-colonial narratives and external influence on strengthening the conflict in Ukrainian society. The changes in perception of surzhyk in the mass linguistic consciousness of Ukrainian society is shown, especially its transformation into one of the markers of Ukrainian identity in the conditions of the war.